Voice handicap index: european portuguese versions, validity, and usefulness - Guimarães, Isabel (2023)
Aims: With regard to the Voice Handicap Index (VHI) in European Portuguese, the aims of this study were to: (i) Identify the versions currently in use; (ii) Analyze the process used for the linguistic cultural adaptation and the clinimetric properties; and (iii) Determine the clinical and scientifc usefulness. Study design: Systematic literature review. Materials and Methods: Two independent researchers searched the databases, open access repositories, and archives of two Portuguese scientifc journals. Clinimetric properties and clinical and scientifc usefulness were analyzed according to the international guidelines for patient reported outcome measures (PROMs). Results: In total, fve questionnaires were identifed in EP: the original VHI, two abbreviated versions - VHI-9i and VHI-10, and two adapted versions - pediatric (pVHI) and VHI for singers (SVHI). The VHI is unique as it provides evidence of all the ten recommended clinimetric properties. Conclusions: The VHI is recommended for clinical assessment and research, while the others have the potential to be recommended.